New shapes and original creations: the dependent nature of the individual in a Nahua community in Mexico - Iorio, Silvia; Badino, Paola; Licata, Marta (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Within of Nahua of Naupan, the impact of acculturation processes by the historical interconnection between different models of medicine has given rise to important revisions and reinterpretations of local medical culture. The main purpose of this article is the observation of dynamics and aspects related to processes of understanding, perception and management of diagnostic categories, as well as the local understanding of the person (the individual) in the rural district of Naupan, located in the North East part of Sierra de Puebla. Methods: The analysis presented in this work is the result of an ethnographic study carried out at the Nahua community (1,614 people) residing in the rural town of Naupan (Huauchinango, Puebla, Mexico). Results: The attention will be given to the synthetic analysis of the local conceptions of certain pathologies and how the individual is seen as an unstable and constantly changing aggregate, situated in a context where health-related issues are clearly linked to different levels of perceived reality. Conclusions: In settings where there are no systems of institutionalized medical knowledge, nosological concepts are seen in a subjective and indeterminate manner, due to the fact that in some cases they also vary considerably depending on the person. Faced with the choice of therapeutic options, the Naupeña population moves between integrating and rejecting medical concepts from different cultural horizons, through a continuous creation of knowhow that they see as more or less organized and transmissible knowledge about disease, treatments and methods of prevention and interpretation.